2021
DOI: 10.3390/mi12091032
|View full text |Cite
|
Sign up to set email alerts
|

Migration Behavior of Low-Density Particles in Lab-on-a-Disc Devices: Effect of Walls

Abstract: The effect of the lateral walls of a Lab-On-a-Disc device on the dynamics of a model system of particles with a density lower than that of the solvent (modelling parasites eggs) is analyzed theoretically and experimentally. In the absence of lateral walls, a particle always moves in the direction of the centrifugal force, while its trajectory is deflected in the tangential direction by the inertial Coriolis and Euler forces. Lateral walls, depending on the angle forming with the radial direction, can guide the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Since the density of parasite eggs is lower than that of the solvent, they move towards the center of rotation during centrifugation. It is worth noting that the revealed behavior occurs mainly near the center of rotation where the centrifugal force is small, and the interplay of the tangential Euler and Coriolis forces and the interaction with the walls could cause the backward motion [27]. Therefore, the undesirable effects occur near the entrance to the FOV, as confirmed by the experimental observations.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…Since the density of parasite eggs is lower than that of the solvent, they move towards the center of rotation during centrifugation. It is worth noting that the revealed behavior occurs mainly near the center of rotation where the centrifugal force is small, and the interplay of the tangential Euler and Coriolis forces and the interaction with the walls could cause the backward motion [27]. Therefore, the undesirable effects occur near the entrance to the FOV, as confirmed by the experimental observations.…”
Section: Introductionsupporting
confidence: 68%
“…The effect of the lateral walls of a LOD device on the dynamics of a model system of particles with a density lower than that of the solvent (modelling parasite eggs) has been analyzed theoretically and experimentally [27]. It has been shown that the trajectory of a particle moving under the action of the centrifugal force is deflected in the tangential direction by the inertial Coriolis and Euler forces, and in this situation, the particle easily reaches the lateral walls of the narrow channel.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The movement of a planetary ball milling device is illustrated in Figure a, which results from the combination of two opposing centrifugal fields generated by rotation and revolution . We assume that the grinding ball is a particle with mass m and that its motion in the planetary ball milling process obeys Newton’s second law of motion F⃗ = m a⃗ = i F⃗ i F⃗ = prefix− m ω⃗ 1 × ( ω⃗ 1 × L⃗ ) m ω⃗ 2 × ( ω⃗ 2 × R⃗ 2 ) 2 m ω⃗ 1 × ( ω⃗ 2 × R⃗ 2 ) m normald ω⃗ 1 normald t × L⃗ + i F⃗ i Here, a⃗ represents the acceleration (eq ), ω⃗ 1 and ω⃗ 2 represent the angular velocities of the revolution and rotation, respectively. L⃗ and R⃗ 2 represent the radii of the revolution and rotation, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%